Links to free: Networks of Policies for Abolition of Contemporary Slave Labor in Brazil. - Monteiro, Lilian Alfaia; Fleury, Sonia (Organizações & Sociedade, 2014)
The aim of this paper was to identify the dynamics of the relationships among political actors in the evolution of public policies to eradicate slave labor. Thus, the study was developed based on literature and field research with interviews of the following actors: MTE, MPT, ILO, CPT, NGO Reporter Brazil, GPTEC and OAB. Data were analyzed using content analysis with a qualitative bias. The results enabled the identification of the actors and their different operating strategies; their perception about the performance of the three powers; and the positioning of the main actors, as well as the design of various networks between the actors involved in the field with their own formats and different insertions in public policy, showing division between networks to combat forced labor and resistance networks, revealing an interplay of forces in the fight against contemporary slavery in Brazil.